Implementasi Media Online Waspada dalam Mengkomunikasikan Berita Edukasi : Studi Kasus: Kantor Waspada Kota Medan - Amaluddin Sauri Harahap; Nursapia Harahap (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research aims to find out “Implementation of Waspada Online Media in Communicating Educational News (Case Study: Waspada Medan City Office)”. The method in this study uses qualitative methods with the form of dataresearch(field research). The results of this study are that 1. The role of alert online media in communicating educational news, it can be concluded that Waspada Daily uses marketing communications such as advertising, sales promotion, public relations, personal selling and direct marketing. 2. Waspada Daily prioritizes establishing good relations with consumers and the community in facing competition with online media. 3. Facing the development of journalism in the digital era like today. This issue is interesting considering that repeatedly world journalism experts predict the death of print mass media every time the onslaught of technological developments occurs from time to time. In the digital age, people who need certain information from all over the world can simply search for it on search engines connected to the internet network anytime and anywhere with sophisticated equipment that is currently growing rapidly.